Experiment Design for Waste Heat Recovery Modeling in Heavy Duty Trucks. Issue 31 (2018) - Galuppo, Francesco; Dufour, Pascal; Nadri, Madiha; Reiche, Thomas; Lemort, Vincent
Abstract: Transient working conditions of a waste heat recovery (WHR) system in a heavy-duty (HD) truck application require the control of internal variables of the thermodynamic Rankine cycle for the final large scale commercial integration of this technology. The intensive test demand and the large number of possible operating points of the HD truck engine suggest paying particular attention to the choice of the engine working points to use for model identification needed in further control design. This paper presents a methodology for the design of the engine working points to test in experiments in order to proceed to an open loop multi-linear and multi-structure model identification task from experimental data.